The Moderating Influence of Religion on the Behavioral Health of Formerly Incarcerated Men - Pezzella, F; Vlahos, S (Springer US, 2014)
Formerly incarcerated persons have been found to sustain disproportionate rates of infectious and chronic diseases that place them at elevated levels of morbidity and mortality. However, prior research has found that religiosity moderates risks for poor health outcomes. We assess the moderating influence of religiosity on non-compliance with health maintenance and risk behaviors found to be robust predictors of poor health. Findings indicated that religiosity was not significantly associated with health maintenance behaviors. However, religiosity did demonstrate a significant negative relationship with reductions in health risk behaviors including marginal reductions in prior substance dependency and significant reductions in opinions on extramarital and unprotected sex practices contrary to prior research findings of the prevalence of high sexual risk behaviors. Findings validate prior research that found this population at sustained risk for illness. However, the study demonstrated a clear inverse relationship between religion and health risk behaviors found to be prevalent among formerly incarcerated men. Results from this exploratory investigation suggest that the moderating influence of religion on high risk behaviors of formerly incarcerated men should be examined over a much longer study period with controls to tease out the unfettered influence of religion. © 2014 Springer Science+Business Media New York.